EXPLORING THE LINK BETWEEN CANNABIS DEPENDENCE AND AMOTIVATION SYNDROME: A CASE SERIES ANALYSIS""EXPLORING THE LINK BETWEEN CANNABIS DEPENDENCE AND AMOTIVATION SYNDROME: A CASE SERIES ANALYSIS - D, MOHANAAPRIYA; BHATTIPROLU, AJAY; NAMBI, SHANTHI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Cannabis use disorder (CUD) is a prevalent substance use disorder associated with various negative consequences, including amotivation syndrome, characterized by reduced goal-directed behavior and social withdrawal. Despite its clinical significance, there remains a gap in understanding the relationship between cannabis dependence and amotivation syndrome. Methods: We conducted a case series analysis to explore the link between cannabis dependence and amotivation syndrome. Four cases of individuals with cannabis dependence presenting with symptoms of amotivational syndrome were identified and analyzed based on clinical features, substance use history, and prognosis. Results: All four cases exhibited clinical features consistent with amotivation syndrome, including apathy, reduced goal-directed behavior, social withdrawal, and impaired executive function. Cannabis use was identified as a common factor among these cases, with varying patterns of consumption and severity of dependence. Prognosis varied among cases, with some showing improvement with treatment while others experienced persistent or worsening symptoms over time. Conclusion: Our case series highlights the association between cannabis dependence and amotivation syndrome, underscoring the need for further research to elucidate the underlying mechanisms and develop targeted interventions. Early identification and intervention for cannabis dependence may prevent the development or progression of amotivation syndrome, thereby improving clinical outcomes and quality of life for affected individuals.